Induction of HLA-DC/DS (LEU 10) antigen expression by human precursor B cell lines (The Rockefeller University Press, 1983)
The expression of HLA-DC/DS antigen detected by the monoclonal antibody Leu 10 was studied in three human precursor and pre-B cell lines (Josh 7, Reh, and Nalm 12). Flow cytometric analysis showed that none of these cell lines stained for the HLA-DC/DS antigen. In the presence of 1.6 X 10(-9) M of 12-O-tetradecanoylporbol-13-acetate (TPA), expression of this antigen was detected. The expression was completed after 168 h of incubation. Iodination of cell surface, immunoprecipitation by Leu 10 antibody, and two-dimensional gel analysis revealed that TPA-treated Josh 7 cells synthesized and expressed a 29,34 kD bimolecular complex with both alpha and beta chains different from those of HLA-DR antigen. Quantitative absorption experiments with cell lysates indicated a greater than 25-fold increase in HLA-DC/DS antigen in TPA-treated cells. With the induction of HLA-DC/DS antigen expression, there are concomitant decreases in the expression of the common acute lymphoblastic leukemia antigen (CALLA) and the enzymatic activity of terminal deoxynucleotidyl transferase. No appreciable changes in HLA-DR and Ig expression were observed. There was also no change in HLA-SB expression as detected by antibody ILR-1. However, DNA synthesis was markedly inhibited by TPA treatment. These results indicate that precursor and pre-B cell lines can be induced to mature in vitro. They also suggest that the expression of HLA-DC/DS antigen which precedes the expression of membrane Ig and follows the HLA-DR expression is relevant to human B cell development and cell interaction.